Routes of administration, reasons for use, and approved indications of medical cannabis in oncology: a scoping review - Billy Vinette; José Côté; Ali El-Akhras; Hazar Mrad; Gabrielle Chicoine; Karine Bilodeau (BMC Cancer, 2022)
Abstract Introduction Some patients diagnosed with cancer use medical cannabis to self-manage undesirable symptoms, including nausea and pain. To improve patient safety and oncological care quality, the routes of administration for use of medical cannabis, patients’ reasons, and prescribed indications must be better understood. Methods Based on the Joanna Briggs Institute guidelines, a scoping review was conducted to map the current evidence regarding the use of medical cannabis in oncological settings based on the experiences of patients diagnosed with cancer and their healthcare providers. A search strategy was developed with a scientific librarian which included five databases (CINAHL, Web of Science, Medline, Embase, and PsycINFO) and two grey literature sources (Google Scholar and ProQuest). The inclusion criteria were: 1) population: adults aged 18 and over diagnosed with cancer; 2) phenomena of interest: reasons for cannabis use and/or the prescribed indications for medical cannabis; 3) context: oncological setting. French- or English-language primary empirical studies, knowledge syntheses, and grey literature published between 2000 and 2021 were included. Data were extracted by two independent reviewers and subjected to a thematic analysis. A narrative description approach was used to synthesize and present the findings. Results We identified 5,283 publications, of which 163 met the eligibility criteria. Two main reasons for medical cannabis use emerged from the thematic analysis: limiting the impacts of cancer and its side effects; and staying connected to others. Our results also indicated that medical cannabis is mostly used for three approved indications: to manage refractory nausea and vomiting, to complement pain management, and to improve appetite and food intake. We highlighted 11 routes of administration for medical cannabis, with oils and oral solutions the most frequently reported. Conclusion Future studies should consider the multiple routes of administration for medical cannabis, such as inhalation and edibles. Our review highlights that learning opportunities would support the development of healthcare providers’ knowledge and skills in assessing the needs and preferences of patients diagnosed with cancer who use medical cannabis.